Grid Connected Solar PV System with SEPIC Converter Compared with Parallel Boost Converter Based MPPT - T. Ajith Bosco Raj; R. Ramesh; J. R. Maglin; M. Vaigundamoorthi; I. William Christopher; C. Gopinath; C. Yaashuwanth (International Journal of Photoenergy)
The main objective of this work is to study the behaviour of the solar PV systems and model the efficient Grid-connected solar power system. The DC-DC MPPT circuit using chaotic pulse width modulation has been designed to track maximum power from solar PV module. The conversion efficiency of the proposed MPPT system is increased when CPWM is used as a control scheme. This paper also proposes a simplified multilevel (seven level) inverter for a grid-connected photovoltaic system. The primary goal of these systems is to increase the energy injected to the grid by keeping track of the maximum power point of the panel, by reducing the switching frequency, and by providing high reliability. The maximum power has been tracked experimentally. It is compared with parallel boost converter. Also this model is based on mathematical equations and is described through an equivalent circuit including a PV source with MPPT, a diode, a series resistor, a shunt resistor, and dual boost converter with active snubber circuit. This model can extract PV power and boost by using dual boost converter with active snubber. By using this method the overall system efficiency is improved thereby reducing the switching losses and cost.